Brexpiprazole for treatment-resistant major depressive disorder. (2nd November 2019) - Fornaro, Michele; Fusco, Andrea; Anastasia, Annalisa; Cattaneo, Carlo Ignazio; De Berardis, Domenico
ABSTRACT: Introduction :Treatment-resistant depression (TRD), seldom interchangeably referred to as 'depression inadequately responding to the standard antidepressant drug, ' carries a significant burden. The atypical antipsychotics represent a popular augmentation strategy for antidepressant-resistant depression, although their efficacy/safety profiles vary across different agents and presentations of depression. Areas covered : This review appraises the evidence supporting the use of brexpiprazole augmentation for major depressive disorder (MDD) adults showing an inadequate response to standard antidepressants, covering the related regulatory affairs, and essential pharmacology. Expert opinion : Brexpiprazole is a 'third-generation' antipsychotic featuring dopaminergic D2 and serotonergic 5-HT1A partial agonism approved by the U.S. Food and Drug Administration for the treatment of MDD, besides schizophrenia in adults. The clinical trials leading to the extended approval of brexpiprazole rely on the definition of 'inadequate response' to antidepressants, which seems to poorly represent the most severe cases of TRD seen in clinical practice. TRD definitions appraised in the literature are likewise inconsistent and questionable from a clinical-standpoint. Compared to aripiprazole, brexpiprazole has lower D2 intrinsic activity, although the latter features a more potent serotonergic 5-HT2A antagonism. The actual propensity of brexpiprazole to induce akathisia and tardive dyskinesia warrants assessment by ad-hoc designed long-term, controlled trials.